MODIFIED ATMOSPHERE PACKAGING OF RASPBERRIES-MAP - Janković, Miodrag; Stevanović, Snežana; Leposavić, Aleksandar (Economics of Agriculture, 2006)
According to statistical data, Serbia is greatest exporter of raspberries at the world. Annually raspberry production is about 100.000 t, and therefrom 80% is exported in frozen state. Among concurrents that owen raspberry place at Europe market are: Chile, Hungary and Poland. These producers, beside frozen raspberry offer also a fresh raspberry in the corresponding packaging, in order to extend shelf life and marketing. According to EU market data fresh raspberry in conform packaging achieve up to 15 EUR fore one kilo. In that case it should consider that except proper packaging and cooling each other treatment and storage is not necessary, in comparison with frozen raspberry export, it can multipi income. In these paper system of packaging is elaborated, type of packaging material and gas mixture in package wherein fresh and cool raspberry export, or MAP (Modified Atmosphere Packaging). By using MAP for raspberry, control growth of Botrytis, removing of ethylene, in combination with low temperature in distribution, shelf life of fresh raspberry can bee extended from 2 to 3 time, in a comparison with standard storage conditions of fresh raspberry in warehouse.